A Mystic Analysis of Alda Merini’s Poetry - Mohammad Hussein Ramezankiaei; Mahtab Alimohammadi Malayeri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
AldaMerini appearsamong those contemporary Italian poets translated into Persian. Merini is a poetess of great renown because her poetry leads readers to the knowledge of a world-wide aspect of literature. With her works, Merini has demonstrated a great intellectual diligence in the condemnation of contemporary society alien to Truth. She becomes the defender of the weak and marginalized people, carrying on this task with courage and without any fear; she tried to carry the flag of truth in favor of the oppressed. Her verses reveal a profound spirituality and also a particular aspect that has always characterized the Sufi culture and literature deeply esteemed and venerated in Persian literature. A great amount of Sufi poetry has been written in Persian and thus people of Persian culture have been fed of this kind of poem in various moments of prayer, sorrow and happiness. This research tires to shed light on Merini’s spirituality concealed in her Sufi poetry. This study is not an attempt of making a comparison but rather an attempt of analyzingMerinian poems under the light of the universal mysticism of Sufism that possesses an incomparable depth with any other literary genre. It is appropriate to put Merini’s poem in contact with the Persian Sufi Farid-adin Attar’s work entitled Manṭiq-uṭ-Ṭayr(The seven valleys of spirituality).